2022
DOI: 10.1155/2022/2416196
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors of Acute Radiation-Induced Lung Injury Induced by Radiotherapy for Esophageal Cancer

Abstract: Objective. To investigate the risk factors of acute radiation-induced lung injury (acute RILI) induced by radiotherapy for esophageal cancer. Methods. A total of 206 patients with esophageal cancer who received radiotherapy in our hospital from January 2017 to March 2020 were selected. The general data such as gender, age, and comorbidities of the patients were collected, as well as the levels of cytokines (TNF-α, TNF-β, and IL-6) in peripheral blood before radiotherapy; radiotherapy dose-related parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…However, these factors showed limited efficiency for individualized RP prediction. As is well known, RT can induce an immune response through the release of pro-inflammatory cytokines and the regulation of immune cells ( 18 , 19 ), while RP has a closed connection with inflammatory cells infiltrated ( 20 , 21 ). Specially, lymphocyte was show to closely related to the risk of RP, with the recruitment of lymphocyte in the process of RP ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these factors showed limited efficiency for individualized RP prediction. As is well known, RT can induce an immune response through the release of pro-inflammatory cytokines and the regulation of immune cells ( 18 , 19 ), while RP has a closed connection with inflammatory cells infiltrated ( 20 , 21 ). Specially, lymphocyte was show to closely related to the risk of RP, with the recruitment of lymphocyte in the process of RP ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%